Accelerated microwave assisted synthesis of alumino-germanate imogolite nanotubes. Issue 109 (14th November 2016) - Avellan, A.; Levard, C.; Chaneac, C.; Borschneck, D.; Onofri, F. R. A.; Rose, J.; Masion, A.
Abstract : Microwave assisted synthesis of Ge-imogolite nanotubes reduced the time required for their growth and shifted their length repartition towards larger values. Abstract : Ge-imogolite nanotubes (Al2 GeO7 H4 ) can be readily obtained in various lengths, chemical compositions and crystallinities, opening up new perspectives for applications. Their classical synthesis includes the nucleation of roof-tile shaped precursors at room temperature followed by a heat promoted growth (typically 95 °C) for at least 4 to 7 days. To circumvent this excessively long synthesis duration, we used microwave assisted heating to accelerate the growth. Micron sized tubes were formed from 1 h at 100 °C, and the best results were obtained for 2 hours at 200 °C, i.e. approximately 100 fold faster when compared to the conventional heating process. Additionally, tube lengths were shifted towards larger values by one order of magnitude, leading to micron sized Ge-imogolites vs. 100 nm with conventional heating. Specific microwave effects as well as mechanisms leading to these longer tubes are also discussed.